2010
DOI: 10.1016/j.foodres.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Seed extracts of Gleditsia triacanthos: Functional properties evaluation and incorporation into galactomannan films

Abstract: In this work, three different extraction procedures were performed in Gleditsia triacanthos seeds in order to obtain extracts that were characterized in terms of the yield of extraction, total phenolic content and antioxidant properties. The extracts have been shown to contain considerable amounts of phenolic compounds (between 4.93 and 12.34 mg galicacid g extract − 1) and antioxidant activity between 18.77 and 71.59%. Different concentrations of one of the extracts (extract presenting simultaneously the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 33 publications
(41 reference statements)
2
28
0
1
Order By: Relevance
“…The WVP values obtained in our study were lower than for other biopolymers films [including whey protein concentrate and CM composite films (0.620-0.678 g mm/kPa h m 2 , , Opuntia ficus-indica L. mucilage-based films (4.96 g mm/kPa h m 2 , Espino-Díaz et al, 2010), whey protein isolate and mesquite gum composite films (2.0 g mm/kPa h m 2 , Osés et al, 2009) whey protein and okra polysaccharide fraction composite films (2.9 g mm/kPa h m 2 , Prommakool, Sajjaanantakul, Janjarasskul, & Krochta, 2011)] but were comparable to galactomannan films (0.235 g mm/kPa h m 2 , Cerqueira, Souza, Martins, Teixeira, & Vicente, 2010), and higher than synthetic films [such as high density polyethylene film (HDPE) (0.0012 g mm/kPa h m 2 ) and polyester film (0.0091 g mm/kPa h m 2 ) (McHugh et al, 1993)]. The differences in results between edible films may be attributed to the hydrocolloid source and its proportion in the final film, film thickness used, as well as differences in test procedure.…”
Section: Water Vapor Permeability (Wvp) Measurementmentioning
confidence: 95%
“…The WVP values obtained in our study were lower than for other biopolymers films [including whey protein concentrate and CM composite films (0.620-0.678 g mm/kPa h m 2 , , Opuntia ficus-indica L. mucilage-based films (4.96 g mm/kPa h m 2 , Espino-Díaz et al, 2010), whey protein isolate and mesquite gum composite films (2.0 g mm/kPa h m 2 , Osés et al, 2009) whey protein and okra polysaccharide fraction composite films (2.9 g mm/kPa h m 2 , Prommakool, Sajjaanantakul, Janjarasskul, & Krochta, 2011)] but were comparable to galactomannan films (0.235 g mm/kPa h m 2 , Cerqueira, Souza, Martins, Teixeira, & Vicente, 2010), and higher than synthetic films [such as high density polyethylene film (HDPE) (0.0012 g mm/kPa h m 2 ) and polyester film (0.0091 g mm/kPa h m 2 ) (McHugh et al, 1993)]. The differences in results between edible films may be attributed to the hydrocolloid source and its proportion in the final film, film thickness used, as well as differences in test procedure.…”
Section: Water Vapor Permeability (Wvp) Measurementmentioning
confidence: 95%
“…Extraction of GAP in neutral conditions was based on the method of a previous researcher with slight modification [7]. The result of this process has been published [6].…”
Section: Preparation Of Gap and Zoementioning
confidence: 99%
“…Based on our knowledge, only limited research exists about the characterization and application of galactomannan as EF and coating compared with other polysaccharides. However, current research on galactomannan has shown a new perspective about the properties and usage of galactomannan for EF and coating, based on the specific property of galactomannan solution which forms a viscous liquid with water even in low concentrations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of galactomannans to form viscous solutions at relatively low concentration is their greatest advantage [17]. Furthermore aqueous solutions of galactomannan are basically neutral [35] and their viscosity is insensitive to pH variations (a broad range from 1 to 10.5); nevertheless some degradation may occur under highly acidic or alkaline conditions [7,35].…”
Section: Ph Valuementioning
confidence: 99%
“…Galactomannans are used in food, pharmaceutical, biomedical, cosmetic, textile and paper industries. Many studies have reported the potential use of galactomannans as thickeners [5], part of mixed systems such as hydrogels [6], emulsion stabilizers in the preparation of films [7] and edible films themselves with enhanced barrier as well as mechanical properties that extend and improve food shelf-life [8,9]. It is also important to highlight the application of galactomannans in the cosmetic industry [10] and as matrix for immobilization of certain biomolecules [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%